Peran Tenaga Penjual Terhadap Tingkat Penjualan Oli Shell Pada PT. Graha Arta Kaltim Sentosa Di Samarinda - Sunarto 3, Sheila Cahyaning Pratiwi Mardiana 2 (EKONOMIA, 2021)
The objectives of this study are as follows:1) To find out the significant positive influence of salesperson attitude to the level of sales of Shell Oil at PT. GAKS in Samarinda, 2) To know the significant positive influence of salespeople' ability on the level of sales of Shell Oil at PT. GAKS in Samarinda, 3) To know the significant influence of the attitude and capability of salespeople together to the level of sales of Shell Oil at PT. GAKS in Samarinda.Data collection is conducted by observation, interview and dissemination of print out questionnaires using a likert scale to measure indicators. The analysis tool used is multiple linear regression with the help of SPSS version 23. The populationÂ using saturated sampling techniques and the number of samples is 30 respondents.The results of the study partially showed that the variable attitude of salespeople has a positive and insignificant effect while the variable ability of salespeople has a positive and significant effect on the level of sales. Simultaneously shows that the variable attitude of salespeople and the ability of salespeople have a significant effect together on the level of sales of Shell Oil at PT. Graha Arta Kaltim Sentosa in Samarinda.